Electronic Document Imaging Systems: Design, Evaluation, and Implementation - Woody, Janet (Information technology and libraries, 1993)
Book review abstract. Westport, Conn.: Meckler, 1993. 183pp. paper, 40 dollars. ISBN 0-89736-840-9. Reviewed by Janet Woody.